Teknologi Budidaya Tanaman Padi (Oryza Sativa L.) Berbasis Pemupukan Organik Dalam Mewujudkan Ketahanan Pangan Di Wilayah Perbatasan RI-RDTL - Erminia Pereira Dos Santos; Desak Ketut Tri Martini; Onesimus Ke Lele; Yosni Kiuk (Politeknik Negeri Lampung., 2024)
Increased plant productivity can be achieved through the development of organic fertilization technology that utilizes local organic matter that is easily accessible to farmers. An example is the use of manure from cow and goat manure, as well as forage such as kirinyuh and gamal. This approach offers a solution to the low productivity of rice in drylands. The use of organic fertilizers in various doses is expected to improve soil nutrient status while increasing rice productivity in dry land. This research was carried out on farmers' land in Ponu Village, Biboki Anleu District, North Central Timor Regency, East Nusa Tenggara, which is located in the RI-RDTL border area, precisely the Oekusi section. The experiment in this study was designed in a Group Randomized Design consisting of 10 treatments. The treatment is No Fertilization (P0D0), 10 tons of cow manure fertilizer (PsD1), 20 tons of cow manure fertilizer (PsD2), 30 tons of cow manure (PsD3), 10 tons of goat manure (PkD1), 20 tons of goat manure (PkD2), 30 tons of goat manure (PkD3), 10 tons of forage (PhD1), 20 tons of forage (PhD2), and Forage fertilizer with a dose of 30 tons (PhD3). Each treatment was repeated 4 times so that there were 40 experimental plots. The results showed that the combination of goat manure treatment with a dose of 30 tons/ha (PkD3) had a better effect than other treatment combinations. This combination of treatments was able to provide the best observation value on several parameters, namely plant height growth, the number of saplings and the number of panicles per clump as well as the production of dry grain weight harvested per plot.